Demeclocycline in the treatment of the syndrome of inappropriate secretion of antidiuretic hormone. Issue 3 (June 1979) - Perks, W H; Walters, E H; Tams, I P; Prowse, K
Abstract : Fourteen patients with the syndrome of inappropriate secretion of antidiuretic hormone (SIADH) have been treated with demethylchlortetracycline (demeclocycline) 1200 mg daily. In 12 patients the underlying lesion was malignant. The serum sodium returned to normal (greater than 135 mmol/l) in all patients after a mean of 8.6 days (SD +/- 5.3 days). Blood urea rose significantly from the pretreatment level of 4.2 +/- 2.3 mmol/l to 10.1 +/- 5.1 mmol/l at ten days (P less than 0.001). The average maximum blood urea was 13.4 +/- 6.8 mmol/l. In four patients the urea rose above 20 mmol/l, and in two of these demecyocycline was discontinued because of thie rise. The azotaemia could be attributed to a combination of increased urea producation and a mild specific drug-induced nephrotoxicity. Discontinuation of demeclocycline in six patients led to a fall in serum sodium, in one case precipitously, and return of the urea towards normal levels. Demeclocycline appears therefore to be an effective maintenance treatment of SIADH, and the azotaemia that occurs is reversible and probably dose dependent.